Guest Editorial Commentary: Statistics: An Intrinsic Part of Everyday Life - Oyedele, Opeoluwa (Namibian Journal for Research, Science and Technology, 2022)
Fast becoming an ever-present reality in our day-to-day lives, statistics play an intrinsic and contemporary role in our everyday activities, especially, in today’s data-driven world. Owning to its definition as the science of collecting, summarizing, presenting and interpreting information, statistics helps us understand the world a little bit better through numbers as well as other quantitative and qualitative source of information. Although statistics originated many centuries ago, its impacts and applications have evolved in recent years as modern statisticians have advanced applications of statistics through innovative, problem-solving approaches, far beyond its historic use by governmental offices to capture censuses in order to track population sizes and growths (Michigan Technological University, 2021). One of these modern statisticians was Sir Ronald Aylmer Fisher (1890 - 1962) who was active as a mathematician, statistician and geneticist. Although trained as an (evolutionary) biologist, Fisher was referred to as the “father of the modern science of statistics” as he single-handedly created the foundations for modern statistical science (Anders, 1998). He further pioneered the design of experiments principles, small samples statistics and the analysis of real data. He went on to published a book titled “Statistical Methods for Research Workers” in 1925, which later became one of the 20th century’s most influential books on statistical methods and even to date. His notable works includes the popularly used F-test, F-distribution, Fisher’s exact test, maximum likelihood estimation, random effects models and analysis of variance, to mention a few. The importance of statistics being relevant to nearly every area of our lives cannot be overemphasized enough, to the extent that all countries over the world have at least one national statistical agency operating within their respective countries that manages critical information related to labour trends, health, education, political campaigns and many more. Statistics has influenced and is still influencing the operations of industries such as the sales and financial markets, profit and non-profit organizations, meteorological services, medical care services, manufacturing, urban planning, education, law, and even social media analytics (to mention a few). In this present world, we as individuals and organizations regularly use statistics to make daily financial and non-financial planning and budgeting decisions that affects our lives. For example, consider the daily forecasted weathers, lending risks at banks, impacts of economy crises, healthcare financial policies, traffic flow operations, investment payoffs, urban planning with respect to population growths and declines, predicting diseases, stock markets, human psychology behaviours, insurance pay-outs, and political election results. All these, and more, are statistics and/or derived from statistics. Another simple life application of statistics is the global daily recorded number of COVID-19 cases, deaths, recoveries and vaccination numbers. As of 23 August 2021, a total of 212,679,403 COVID-19 cases were recorded, with 4,446,610 deaths and 190,301,359 recoveries, with majority of these cases reported in the United States of America, India, Brazil, United Kingdom, France, Russia, Turkey and Italy (Worldometer, 2021). Again, all these basic figures were all compiled through the use of statistics in various regions, states, countries, provinces and continents all over the world. Thus, statistics is heavily used in many different fields for a variety of applications as showcased in this journal issue.